Revisiting the designing criteria of advanced solid electrolyte interphase on lithium metal anode under practical condition. (May 2021) - Yuan, Shouyi; Weng, Suting; Wang, Fei; Dong, Xiaoli; Wang, Yonggang; Wang, Zhaoxiang; Shen, Cai; Bao, Junwei Lucas; Wang, Xuefeng; Xia, Yongyao
Abstract: Reducing the ratio of Negative/Positive ratio (N/P ratio) is critical to increase the energy density of Li metal batteries (LMBs). Typically, stable Li deposition with high Coulombic Efficiency (CE) can be easily achieved with ether-based electrolyte, but the low oxidation stability restrains its applications in batteries with high-voltage cathodes. Herein, we performed cryogenic electron microscopy (Cryo-EM), in-depth X-ray Photoelectron spectrum (XPS) and Atomic Force Microscopy (AFM) on the Solid Electrolyte Interphase (SEI) layer formed in carbonate-based electrolyte and ether-based electrolyte to probe the characteristics of good SEI layer and aimed to design good SEI layer in carbonate-based electrolyte by tuning the electrolyte composition. The results suggest that the organic composition in the SEI layer determine the CE of LMBs. Further theoretical calculation suggests the highly reactive nature of carbonate molecules with Li results in the organic-rich SEI layer with low elastic modulus. On the basis of these insights, we propose design methodology for an advanced SEI layer in carbonate electrolyte by tuning the electrolyte composition. The designed SEI exhibits multilayer structure with a dense inorganic inner layer. Consequently, a 4 V full cell was assembled and delivered a high energy density of 760 Wh/kg (calculated based on the weight of cathode and anode) with long cycle life of 200 cycles in carbonate electrolyte. Graphical Abstract: Cryo-EM combined with AFM and In-depth XPS establish the correlation between the CE and the property of SEI. As a result, the criteria for designing the advanced SEI are proposed. Excellent performance is achieved with designed SEI layer. ga1 Highlights: Cryo-EM, AFM and In-depth XPS establish correlation between CE and property of SEI. DFT calculation investigate the reactivity between solvents and Li metal. The designing criteria for advanced SEI in carbonate-electrolyte is proposed. Long cycle life of NCM811||Li (N/P = 1) over 200 times is achieved with designed SEI in carbonate electrolyte.